Determinants of Quality of Work Life: The Case of Small and Medium Enterprises in Kogi State - Emmanuel, M. E.; Orugun, J. J.; Audu, K. (International Journal on Economics, Finance and Sustainable Development, 2022)
The study aimed at determinants of quality of work life in Small and Medium Enterprises in Kogi State. The survey research design was applied. A multi-stage sampling technique was adopted to choose the sample size of 365. Data were gathered and analyzed using inferential analytical technique. Regression analysis was used. Finding showed that quality work time has strong effect on QWL of SMEs’ employees in Kogi State (R2- 0.5128). Finding further showed that good work conditions have effects on the QWL of SMEs’ employees in Kogi State (R2- 0.9868). The study concluded that quality work time strongly determines the QWL of SMEs’ employees in Kogi State. Good work conditions strongly determine the QWL of SMEs’ employees in Kogi State. The study recommended that to improve employees' quality of life in Kogi State, SME owners should ensure that employees have considerable work time, and that they should adopt work scheduling autonomy and decision-making autonomy.